2017
DOI: 10.3892/ol.2017.7476
|View full text |Cite
|
Sign up to set email alerts
|

miR‑125b regulates the drug‑resistance of breast cancer cells to doxorubicin by targeting HAX‑1

Abstract: MircroRNAs (miRNAs) are considered as essential regulators in the tumorigenesis and chemoresistance of multiple cancer types. In the present study, it was demonstrated that the expression levels of miR-125b were significantly downregulated in the tissues of patients with breast cancer (BC), as well as the BC cell lines in vitro. To study the association between chemoresistance and miR-125b in BC, doxorubicin (DOX)-resistant MCF-7 (MCF-7/R) cells were established, and gain- and loss-of-function experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The cytotoxic mechanism of DOX is dependent on apoptotic pathway and involves the inhibition of DNA or RNA synthesis following penetration into DNA. The resistance of breast cancer cells to apoptotic pathways has reduced the clinical effectiveness of this chemotherapeutic drug (49). In the present study, we showed that miR-154 increased the cellular response to DOX and cell survival is significantly decreased when DOX treatment was combined with up-regulation of miR-154.…”
Section: Luciferase Reporter Assay Verifying the Predicted Interactiomentioning
confidence: 47%
See 1 more Smart Citation
“…The cytotoxic mechanism of DOX is dependent on apoptotic pathway and involves the inhibition of DNA or RNA synthesis following penetration into DNA. The resistance of breast cancer cells to apoptotic pathways has reduced the clinical effectiveness of this chemotherapeutic drug (49). In the present study, we showed that miR-154 increased the cellular response to DOX and cell survival is significantly decreased when DOX treatment was combined with up-regulation of miR-154.…”
Section: Luciferase Reporter Assay Verifying the Predicted Interactiomentioning
confidence: 47%
“…miR-133b has also been found to be functionally involved in the resistance of breast cancer cells to DOX and the intratumoral delivery of this miRNA increased the treatment response to DOX in DOX-resistant xenografts (51). miR-125b has also been introduces as another regulator of DOX-resistance in breast cancer cells via targeting hematopoietic cell-specific protein 1-associated protein X-1 (HAX-1) (46,49). NAMPT overexpression has been shown to be associated with poor treatment response to chemotherapeutic agents including doxorubicin, etoposide, fluorouracil, paclitaxel, and phenylethyl isothiocyanate (52).…”
Section: Luciferase Reporter Assay Verifying the Predicted Interactiomentioning
confidence: 99%
“…Specifically, various studies have confirmed the expression changes of miR-125b in a variety of cancer tissues and cells. For example, miR-125b as a tumor suppressor gene was downregulated in breast cancer tissues and cells [19], and miR-125b expression in gastric cancer tissues and cells was also significantly downregulated [20]. In this study, it was found that the expression level of miR-125b in GCT tissues and cells was also significantly downregulated.…”
mentioning
confidence: 49%
“…Studies have reported that overexpression of HAX-1 is usually observed in multiple human cancers. Furthermore, overexpression of HAX-1 has been reported to induce resistance to many chemotherapeutic drugs [32,33]. HAX-1 has become an important target in the chemotherapy.…”
Section: Discussionmentioning
confidence: 99%